Value Vectors of Russian Literature: Nizhny Novgorod Text of Russian Literature - Elena M. Dzyuba; Victoria T. Zakharova (Studia Litterarum)
The article analyzes the current trends in the field of “supertext” studies, summarizes the reflection on the “Nizhny Novgorod text of Russian literature,” as well as border chronotopes, carried out in the period from 2007 to the present. Authors of the article indicate the main directions of research, such as the identification and description of the sacred toposes of the Nizhny Novgorod land, the comprehension of the value vectors of Russian literature, which were configured in a number of stable images: the images of the city of Kitezh, the Volga, the Diveevsky and Sarov sacred toposes, the image of Seraphim of Sarov. The review article presents the representative characteristics of the national-regional component. Theese features establish the relationship of creativity with the cultural and historical geospace, which appears as the spiritual homeland of the writer (protopop Avvakum, M. Gorky, E. Chirikov, etc.). An important component of literary discourse is the national image-character, which retains positively marked, sometimes ideal features (from the life of Alexander Nevsky to the heroes of E. Dolmatovsky’s “Sormovskaya Lyric”). The article outlines prospects for further research.